Mengenal Metode Ilmiah : PENGERTIAN METODE ILMIAH, PEMBAGIAN METODE ILMIAH, PENJELASAN ILMIAH, LANGKAH DAN PROSEDUR DALAM METODE ILMIAH, FRANCIS BACON: PERINTIS METODE ILMIAH, SIKAP ILMIAH - Ramadhani, Mutiara; Meyniar Albina (Cemara Education and Science, 2025)
The scientific method is a systematic approach to research that is used to obtain valid and reliable knowledge. This article discusses how philosophical thinking supports the development of the mindset in the scientific method, as well as the relationship between the two. between the two. The research was conducted using the literature study method from the sources of books and online research. The scientific method is defined as a series of steps such as observation, hypothesis formulation, experimentation, data analysis, and conclusion drawing, which aims to produce objective and accountable findings. Scientific explanations emphasize objectivity, empiricism, replicability, and systematic structure to ensure that research results can be tested. structure to ensure that research results are testable and reliable.